THE ACTUALIZATION OF THE CONCEPT «FREE FINDING LAW» IN THE WORKS OF EUGEN EHRLICH - HURALENKO, N. (Ehrlich's Journal, 2023)
In this article the author questions the role of Eugen Ehrlich’s sociological jurisprudence in contemporary debates about legal pluralism. This dualist understanding of law was not typical for Ehrlich who considered that law always manifests itself as a unified social integrity, though it consists of many social orders. Law can be conceptually divided into two logical categories: official law (the law of a state and lawyers) and living (social) law. Neither was Ehrlich inclined to advocate for mechanical transformation of facticity into normativity – this requires additional creative work of lawyers. From this point of view, it is not practicable to use Ehrlich’s socio-legal theory for justification of the project of anthropological jurisprudence to include all normative systems of social regulation in the category of law under the slogan of legal pluralism. Citing Ehrlich as one of the founding fathers of legal pluralism is not undisputable because legal pluralism itself is not a unified scientific doctrine, and many assertions of legal pluralists contradict Ehrlich’s scientific position. Ehrlich was not inclined to undermine the role of law and judiciary in legal reality, which sometimes is typical for some legal pluralists.